Investigating the Learning of Pragmatics across Ages and Contexts. Salazar-Campillo, P. and Codina-Espurz, V. (2019). Leiden: Brill, 260 pages, ISBN: 978-9-004-40785-5. - Hernández, Tamara (Porta Linguarum Revista Interuniversitaria de Didáctica de las Lenguas Extranjeras, 2020)
Book review: Investigating the Learning of Pragmatics across Ages and Contexts. Salazar-Campillo, P. and Codina-Espurz, V. (2019). Leiden: Brill, 260 pages, ISBN: 978-9-004-40785-5.